2013
DOI: 10.1007/s10875-013-9972-4
|View full text |Cite
|
Sign up to set email alerts
|

Renal Amyloidosis in a Patient with X-linked Agammaglobulinemia (Bruton’s Disease) and Bronchiectasis

Abstract: We present a patient with Bruton's disease and bronchiectasis who developed renal AA amyloidosis a finding rarely reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…Gonzalo‐Garijo et al . reported a patient with BTK deficiency who developed renal amyloidosis and could not maintain trough serum IgG, but the present patient's urinalysis was normal. Therefore, we investigated the possibility of protein leakage from the intestinal membrane and abnormal FcRn function.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Gonzalo‐Garijo et al . reported a patient with BTK deficiency who developed renal amyloidosis and could not maintain trough serum IgG, but the present patient's urinalysis was normal. Therefore, we investigated the possibility of protein leakage from the intestinal membrane and abnormal FcRn function.…”
Section: Discussioncontrasting
confidence: 66%
“…This clinical course led us to suspect other causes for the loss of IgG, such as a nephritic syndrome or protein-losing gastroenteropathy. Gonzalo-Garijo et al reported a patient with BTK deficiency who developed renal amyloidosis and could not maintain trough serum IgG, 5 but Fig. 1 Endoscopy of the intestine (from the rectum to the ileocecal region) was nearly normal, but in some areas the intestine appeared slightly fragile and susceptible to bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The search yielded ninety citations, of which idiopathic bronchiectasis, cystic fibrosis, bronchiectasis in immunodeficiencies and Kartagener's syndrome were identified as etiologies of secondary amyloidosis. [ 9 10 11 ] ABPA as a cause of secondary amyloidosis has been reported only once in the literature [ Table 1 ]. [ 12 ] A common feature among the previous reported patients includes the presence of asthma and ABPA for at least two decades before the diagnosis of secondary amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and treatment of bowel infections may decrease the risk of inflammatory bowel disease. Renal AA amyloidosis had been reported in 38-year-old patient with Bruton's disease [103].…”
Section: Complicationsmentioning
confidence: 99%